ANDENESFISK II ou la pêche dans l'Océan Arc:que - Durand, Jean-Pierre (HAL CCSD, 1968)
International audience Andenesfisk II is is the name of the trawler that will allow us to share the hard life of fishermen for 10 days. Its home port is Andenes, a small town in the northern Lofoten Islands, which border northern Norway. We're a few hundred kilometers north of the Arctic Circle; no agriculture, little industry, every inhabitant is dependent on the sea. Every town and village has its own fishing companies, fish dryers and canning factories that flood the European market. The sea is everywhere: if it creeps inland, in the enchanting fjords, it also conditions family life, with father and son going out to sea while mother and daughter work in the cannery. If the village is too small to support an industry, the work is done as a family: the men sail, while the women empty and wash the fish; others salt and dry them, sheltered from the seagulls, on the huge racks dotted along the seashore: Norway lives on the Ocean. But the sea is a difficult partner to live and work with. Its rolling blades bury you forever. Its salty breeze chisels your face. It wears down a man, the fisherman. Andenesfisk Il est le nom de ce chalutier qui va nous permettre de partager, pendant 10 jours, la dure vie des pêcheurs. Son port d'attache se nomme Andenes, petite ville du nord des Iles Lofoten qui bordent le nord de la Norvège. Nous sommes à quelques centaines de kilomètres au nord du cercle polaire aucune agriculture, peu d'Industrie, chaque habitant est tributaire de la mer. Chaque ville, chaque village, possède ses compagnies de pêche, ses séchoirs à poisson, ses conserveries qui inondent le marché européen. La mer est partout : si elle s'insinue au milieu des terres, dans les fjords enchanteurs, elle conditionne aussi la vie de famille, le père et le fils allant en mer pendant que mère et fille travaillent à la conserverie. Si le village est trop petit pour faire vivre une industrie, le travail se fait en famille : les hommes voguent, tandis que les femmes vident et lavent les poissons d'autres les salent et ...